The Non-Survival Effects of Glial Cell Line-Derived Neurotrophic Factor on Neural Cells - Cortés, Daniel; Carballo-Molina, Oscar A.; Castellanos-Montiel, María José; Velasco, Iván (Frontiers in Molecular Neuroscience, 2017)
Glial cell line-derived neurotrophic factor (GDNF) was first characterized as a survival-promoting factor for dopaminergic neurons. Afterwards, other cells were also discovered to respond to GDNF not only as a survival factor but also as a factor supporting other cellular functions, such as proliferation, differentiation, maturation, neurite outgrowth and other phenomena that have been less studied than survival and are now more extendedly described here in this review. During development, GDNF favors the commitment of neural precursors towards dopaminergic, motor, enteric and adrenal neurons; in addition, it enhances the axonal growth of some of these neurons. GDNF also induces the acquisition of a dopaminergic phenotype by increasing the expression of Tyrosine Hydroxylase, Nurr1 and other proteins that confer this identity and promote further dendritic and electrical maturation. In motor neurons, GDNF not only promotes proliferation and maturation but also participates in regenerating damaged axons and modulates the neuromuscular junction at both presynaptic and postsynaptic levels. Moreover, GDNF modulates the rate of neuroblastoma and glioblastoma cancer cell proliferation. Additionally, the presence or absence of GDNF has been correlated with conditions such as depression, pain, muscular soreness, etc. Although, the precise role of GDNF is unknown, it extends beyond a survival effect. The understanding of the complete range of properties of this trophic molecule will allow us to investigate its broad mechanisms of action to accelerate and/or improve therapies for the aforementioned pathological conditions.